Thermal Fluctuations Yield Sex-Specific Differences of Ingestion Rates of the Littoral Mysid Neomysis integer - Hennigs, Laura M.; Bergunder, Konstanze; Sperfeld, Erik; Wacker, Alexander (Frontiers in Marine Science, 2022)
Shallow aquatic environments are characterized by strong environmental variability. For ectotherms, temperature is the main driver of metabolic activity, thus also shaping performance. Ingestion rates in mysids are fast responses, influenced by metabolic and behavioral activity. We examined ingestion rates of the mysid Neomysis integer, collected in the Baltic Sea, after one-week exposure to different constant and fluctuating temperature regimes (5, 10, 15, 20°C and 9 ± 5, 14 ± 5°C, respectively). To investigate possible differences between sexes, thermal performance curves (TPCs) were established for female and male mysids based on ingestion rates measured at constant temperatures. TPCs of ingestion rates at constant temperatures differed between sexes, with female mysids showing a higher total ingestion rate as well as a higher thermal optimum compared to male mysids. Females showed reduced ingestion rates when exposed to fluctuating temperatures around their thermal optimum, whereas ingestion of male mysids was not reduced when exposed to fluctuating temperatures. The observed sex-specific differences might be related to potentially higher lipid and energy demands of the females. We suggest future studies should investigate males and females to improve our understanding about impacts of environmental variability on natural populations.